A Comparison between the Effectiveness of Platelet-Rich Plasma Injection and Corticosteroid Injection in Plantar Fasciitis Patients: A Systematic Review - Fikri Rasikh Pritanto; Rwahita Satyawati; Mouli Edward; Rr. Indrayuni Lukitra Wardhani (Indian Journal of Forensic Medicine & Toxicology, 2022)
A systematic review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses chart(PRISMA) was used in this study. About 7 articles have been included. A month post-injection, corticosteroidinjection reduced pain more than PRP injection (Mean: 1.22; 95% CI:-1.10 to 3.54; p=0.30).However, PRP injectionreduced pain significantly more than corticosteroid injection in three months after injection (Mean: -0.77, 95%CI:-1.46 to -0.96; p=0.03), and in six months later (Mean:-1.22, 95% CI:-2.02 to -0.42; p=0.003). The effectivenessdifference between Platelet-Rich Plasma injection and corticosteroid injection in patients with plantar fasciitisvaries depending on peak period and facial thickness.